Universiti Malaysia Pahang academics receive awards and prizes - Irene, Wei Kiong Ting (2019)
Universiti Malaysia Pahang (UMP) recently awarded Bitara Scholar Awards (BSA) (a.k.a. Anugerah Cendikia Bitara in Malay) to its faculty members during an award-giving ceremony at the Zenith Hotel in Kuantan, Malaysia. This ceremony, which was held on April 12, 2019, marks the increasingly more robust think tank in research and development, alongside innovation and advancement at UMP.